Association between enjoyment factor and physical activity level among tertiary education students / Muhamad Noor Mohamed ... [et al.] - Mohamed, Muhamad Noor; Mohd Sani, Nur Qistina Abrizah; A Rahman, Muhammad Wafi; Saiful Annur, Muhamad Safiq; Mazaulan, Mardiana; Razak, Mohd Aizzat; Md Radzi, & Noor Azila Azreen (Universiti Teknologi MARA, 2022)
Enjoyment plays an important key role in the involvement of physical activity. The purpose of the present was to determine the relationship between enjoyment factors and physical activity level among students in UiTM Alor Gajah.